Friday

April 18, 2014

April 18, 2014

Posted by **Joseph B.** on Saturday, January 13, 2007 at 12:55am.

I will one as an example.

sqrt(3x + 10) =x+4 I hope that is what you meant. When you dont use parenthesis in problems it can lead ot miscommunications.

square both sides:

3x + 10 = x^2 + 8x + 16

gathering terms then

x^2 + 5x +6 =0

(x+3)(x+2)=0

x= -2 9r x=-3

I will be happy to critique your work thinking on the others.

I believe that the answer to the square root of x^2 + 3x = x-3 is X = 3, x=-3 but I'm not sure. I believe the answer to the square root of 8x -2 = the square root of 2x is x=2 again I'm not sure.

I believe that the answer to the square root of x^2 + 3x = x-3 is X = 3, x=-3 but I'm not sure. I believe the answer to the square root of 8x -2 = the square root of 2x is x=2 again I'm not sure.

**Related Questions**

Math ~CHECK MY ANSWER~ - 1) Which of these is a rational number? a. Pi b. Square...

Algebra - I need help on these kinds of radical problems. Once I get the ...

Math ~CHECK MY ANSWERS~ - 1) Which of these is a rational number? a. Pi b. ...

Pre-Calculus - (not sure how to type square root of) square root of 3x - 4 = (x-...

calculus - 6. What is the derivative of y = square root of 3x ? a.dy/dx = square...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

Math simplifying mixed radicals - Please help me simplify these following mixed...

Algebra - Rationalize each expression by building perfect nth root factors for ...

algebra - 1.)correct 2.)wrong---> the first term is wrong 4(3a^2)^2 = 36a^4 3...

ALGEBRA - 1, Factor each expression x^2 - 10x - 24 A. (x + 4)(x - 6) B. (x + 6)(...